Do Personally Tailored Videos in a Web-Based Physical Activity Intervention Lead to Higher Attention and Recall? – An Eye-Tracking Study - Alley, Stephanie; Jennings, Cally; Persaud, Nayadin; Horsley, Mike; Plotnikoff, Ronald C.; Vandelanotte, Corneel (Frontiers in Public Health, 2014)
Over half of the Australian population does not meet physical activity guidelines and has an increased risk of chronic disease. Web-based physical activity interventions have the potential to reach large numbers of the population at low-cost, however issues have been identified with usage and participant retention. Personalized (computer-tailored) physical activity advice delivered through video has the potential to address low engagement, however it is unclear whether it is more effective in engaging participants when compared to text-delivered personalized advice. This study compared the attention and recall outcomes of tailored physical activity advice in video- vs. text-format. Participants (n = 41) were randomly assigned to receive either video- or text-tailored feedback with identical content. Outcome measures included attention to the feedback, measured through advanced eye-tracking technology (TobiiX 120), and recall of the advice, measured through a post intervention interview. Between group ANOVA’s, Mann–Whitney U tests and chi square analyses were applied. Participants in the video-group displayed greater attention to the physical activity feedback in terms of gaze-duration on the feedback (7.7 vs. 3.6 min, p < 001), total fixation-duration on the feedback (6.0 vs. 3.3 min, p < 001), and focusing on feedback (6.8 vs. 3.5 min, p < 001). Despite both groups having the same ability to navigate through the feedback, the video-group completed a significantly (p < 0.001) higher percentage of feedback sections (95%) compared to the text-group (66%). The main messages were recalled in both groups, but many details were forgotten. No significant between group differences were found for message recall. These results suggest that video-tailored feedback leads to greater attention compared to text-tailored feedback. More research is needed to determine how message recall can be improved, and whether video-tailored advice can lead to greater health behavior change.